Tailoring of Aqueous-Based Carbon Nanotube–Nanocellulose Films as Self-Standing Flexible Anodes for Lithium-Ion Storage - Nguyen, Hoang Kha (Nanomaterials (Basel), 2019)
An easy and environmentally friendly method was developed for the preparation of a stabilized carbon nanotube–crystalline nanocellulose (CNT–CNC) dispersion and for its deposition to generate self-standing CNT–CNC composite films. The composite films were carbonized at different temperatures of 70 °C, 800 °C, and 1300 °C. Structural and morphological characteristics of the CNT–CNC films were investigated by X-ray diffraction (XRD), Raman spectroscopy, and scanning electron microscopy (SEM), which revealed that the sample annealed at 800 °C (CNT–CNC(800)) formed nano-tree networks of CNTs with a high surface area (1180 m(2)·g(−1)) and generated a conductive CNC matrix due to the effective carbonization. The carbonized composite films were applied as anodes for lithium-ion batteries, and the battery performance was evaluated in terms of initial voltage profile, cyclic voltammetry, capacity, cycling stability, and current rate efficiency. Among them, the CNT–CNC(800) anode exhibited impressive electrochemical performance by showing a reversible capacity of 443 mAh·g(−1) at a current density of 232 mA·g(−1) after 120 cycles with the capacity retention of 89% and high rate capability.